STRATEGI PENINGKATAN MUTU GURU SEKOLAH DI LINGKUNGAN PESANTREN - Apud Apud (Adaara: Jurnal Manajemen Pendidikan Islam, 2020)
This paper aims to describe the strategic efforts in improving the quality of school teachers in the pesantren environment, the problems of improving the quality of school teachers in the pesantren environment, the efforts and strategic steps of pesantren leaders in improving the quality of school teachers. The research method uses a descriptive-qualitative approach. Data collected through interviews, observations, and documentation. Data were then analyzed using Miles and Huberman analysis models. The results showed that the quality of school teachers in the pesantren environment could be done by fostering teacher quality, supervising teacher quality, providing facilities and infrastructure, planting commitments, and providing benefits.